The Watched Towers : Creating disjunction in a river of movement - Begg, Imraan (School of Architecture, Planning and Geomatics, 2014)
This dissertation is on how architecture can heighten the experience of a route through disjunction and weathering. My motivation for the route is driven by my fascination with movement along an existing spine, which stretches 700 metres from Woodstock station to the harbours edge. The route crosses eight different types of private and public transport modes offering different options. The route is made up of a series of existing 'disjunctions', which incorporates, inclines and declines including a 360 metre continuously raised footbridge. The approach uses the principles of Tschumi's 'superimpositions' to create disjunction in the architecture, together with the effects of natural and social weathering, to heighten the experience of the route. The project approach combines the existing layers of movement (the route), points (moments of intensity) and surfaces (weathering, social and natural) to activate the existing spine. Furthermore, it draws from the historical reference of the 'French lines' which once existed as fortifications separating Woodstock from the CBD. A series of pavilions designed to work within respective locations, using natural and social interaction to generate character through the architecture over time. Each pavilion acts as a regular moment in the landscape with typical and specific functions providing security and infrastructure over the entire route. The result is a route driven essentially by commuter movement, but disjoined at points to allow for physical and social interaction and alternative experience in the spaces. Moments of delay, rerouting, stopping etc. exist, at the same time allowing for the architectural experience of the route to manifest character over time. These moments further use the effect of environmental weathering on the buildings aesthetic as a continuous generator of character.